Within-day improvement in a behavioural display: wild birds 'warm up'. (February 2017) - Schraft, Hannes A.; Medina, Orlando J.; McClure, Jesse; Pereira, Daniel A.; Logue, David M.
Abstract : Motor performance describes the vigour or skill required to perform a particular display. It is a behaviourally salient variable in birdsong and other animal displays, but little is known about within-individual variation in performance over short timescales. The metric 'frequency excursion' (FEX) quantifies birdsong performance as cumulative frequency modulation per unit time. We measured FEX in a large sample of recordings from free-living male Adelaide's warblers, Setophaga adelaidae . Our objectives were to quantify natural variation in performance and test the hypotheses that performance (1) improves as a function of recent practise, (2) decreases over consecutive repetitions of a single song type, (3) improves with rest between songs, (4) varies by singing mode and (5) changes during vocal interactions with neighbours. We found significant variation in performance among individuals and song types. Consecutive repetition of a song type, rest between songs, singing mode and vocal interaction did not strongly affect performance. Performance consistently increased with song order, however, indicating that males warm up during morning singing. This is the first demonstration of such an effect in a sexual display. The warm-up effect may explain the prevalence of intense dawn singing in birds (dawn chorus), if rivals engage in an arms race to warm up. Highlights: Birdsongs with rapid frequency changes are said to have 'high performance'. The performance of Adelaide's warbler songs improves during morning singing. The improvement is best explained by within-day practice, suggesting birds warm up. This warm-up effect could explain why birds sing intensely at dawn.